Perkembangan Pendidikan di Yayasan Pondok Pesantren Darul Ihsan 2000-2022 - -, Ayu Rena Fitriana; Nyong Eka Teguh Iman Santosa (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
This article discusses the development of education at Pondok Pesantren Darul Ihsan Foundation, 2000-2022. It limits to three questions namely (1) the history of the estabilishment of the Foundation , (2) the development of its educational institutions, (3) and the driving and hindering factors for its development. This study uses a diacronic historical approach and John Obert Voll theory on Continuity and Change and Robbins theory of leadership. This article concludes that (1) the Darul Ihsan Islamic boarding school foundation was started by Kiai Mulyadi in 1991. It started with a small room for learning Al-Qur’an which was held at Abah Ihsan's house. Subseque has developed to have many education programs. (2) The development of this foundation began in 2000. Starting from the establishment of STAI Al-Azhar, the foundation has increasingly developed its formal educational institutions, including SMA, SMP, KB, TK, SMK, MI, MTS, and MA. (3) there are several factors that influenced the development of the foundation. Including the enforcing and resisting ones.